IPTEKS BAGI MASYARAKAT (IBM) KELOMPOK PENGOLAHAN LIMBAH PLASTIK, KELURAHAN PORIS PLAWAD, KECAMATAN CIPONDOH, KOTA TANGERANG - Arrozi, MF (Jurnal Pengabdian Masyarakat AbdiMas, 2016)
AbstractHome plastic seed industry is a potential entrepreneur side activity that can increase the income of families in Cipondoh. Manufacture of plastic resin made with a small economic scale without causing error planning effort. This happens because the mastery of knowledge in the production process costing, accounting and reporting highly controlled home industry. These conditions require community service to add value to a home industry in determining product costing, cost price calculation, and calculation of production cost allocation. Thus, home industry is able to be independent economically and education. The purpose of community service is improving their skills in planning and development, costing the production process of plastic resin, and reporting cost price. The scope of activity is the training and management of product pricing plastic seed, determining the selling price of products, as well as business accounting home industry. The method of community service is done by action approach, quality awareness, as well as rapid rural appraisal through socialization to improve the knowledge of managers of domestic industry through the provision of lectures, counseling, and demonstrations to groups of small enterprises. Then proceed with the training and mentoring to draw up an action plan to address the problem of planning and determining the cost of production and cost of the product report. The results is the formation of community service manual for the procedure for the determination of the accounting system unit cost of products, and the formation of statements cost of the product.Keywords : determination of cost, selling priceAbstrakHome industry biji plastic merupakan potensi wirausaha kegiatan sampingan yang dapat meningkatkan pendapatan keluarga di Kecamatan Cipondoh.Â  Pembuatan biji plastik dilakukan dengan skala ekonomi kecil tanpa perencanaan sehingga menyebabkan kesalahan usaha. Hal ini terjadi karena penguasaan pengetahuan costing dalam proses produksi, serta pelaporan akuntansi home industry sangat tidak dikuasai. Kondisi ini memerlukan pengabdian masyarakat untuk memberi nilai tambah bagi home industry dalam menentukan costing produk, perhitungan harga pokok, dan perhitungan alokasi biaya produksi. Sehingga, home industry mampu untuk mandiri secara ekonomis dan edukasi.Tujuan pengabdian masyarakat adalah meningkatkan ketrampilan dalam perencanaan dan pengembangan, costing proses produksi biji plastik, dan pelaporan harga pokok. Lingkup kegiatan adalah pelatihan dan pengelolaan penentuan harga produk biji plastic, penentuan harga jual produk, serta akuntansi bisnis home industry. Metoda pengabdian masyarakat ini dilakukan dengan pendekatan action, quality awareness, serta rapid rural appraisal melalui sosialisasi untuk meningkatkan pengetahuan pengelola industri rumah tangga melalui pemberian ceramah, penyuluhan, dan demonstrasi kepada kelompok usaha kecil. Kemudian dilanjutkan dengan pelatihan dan pendampingan untuk menyusun rencana tindak dalam mengatasi masalah perencanaan dan penentuan harga pokok produksi dan laporan harga pokok produk. Hasil pengabdian masyarakat adalah terbentuknya panduan manual prosedur sistem akuntansi untuk penentuan unit cost produk, dan terbentuknya laporan harga pokok produk.Kata Kunci: penentuan harga pokok, penentuan harga jual